Effects of diatoms on erosion and accretion processes in saltmarsh inferred from field observations of hydrodynamic and sedimentary processes. Issue 8 (9th September 2020) - Chen, Dezhi; Li, Mingliang; Zhang, Yiyi; Zhang, Longhui; Tang, Jieping; Wu, Hao; Wang, Ya Ping
Abstract: Microphytobenthos influence sediment dynamics via their growth and covering on the surface sediment of saltmarshes. To understand the sediment transport and morphological changes resulting from microphytobenthos in a saltmarsh, two parallelly located sites were established to measure the hydrodynamic forces, sediment characteristics and microphytobenthos properties both in winter and summer. Diatoms were not observed at any of the two sites in winter because of their growth cycles. In summer, however, diatoms were found in both sites, with a chlorophyll a (Chl‐a) concentration of 4.1 μg/g in the surficial sediment at the unvegetated site and a Chl‐a concentration of 1.4 μg/g at the vegetated site. Interactions between diatoms and fine particle accumulation induced positive feedbacks between the seabed stable states and the growth of diatoms. Furthermore, the critical erosion threshold value in the vegetated area was 0.33 N/m 2, whereas the value in the adjacent unvegetated area reached up to 0.43 N/m 2 because of the dense diatom armouring in summer, which increased 50% and 126% critical erosion threshold values than those at the corresponding sites in winter. Consequently, net sediment accumulation occurred in the unvegetated area in summer but opposite to that in winter. These results reveal that high coverage of diatoms contributes to substantial impacts on bed erodibility and sedimentary processes, which is vital for the understanding of the morphological evolution in saltmarshes, and provide valuable suggestions for coastal saltmarsh reconstruction.